Newly emerging metronidazole-resistant Clostridioides difficile PCR ribotype 955 identified in Poland, 2021 to 2023 but not in Czechia, 2012 to 2023 and Slovakia, 2015 to 2023 - Hanna Pituch (Eurosurveillance)
Background On 29 January 2024, the European Centre for Disease Prevention and Control distributed an alert about a metronidazole-resistant Clostridioides difficile outbreak of PCR ribotype (RT) 955 in England. Aim We aimed to investigate the presence of RT955 in Czech, Slovak and Polish C. difficile isolates and evaluate different culture media for detecting its metronidazole resistance. Methods Isolates with binary toxin genes identified as ‘unknown’ by the WEBRIBO PCR ribotyping database up to 2023 were re-analysed after adding the RT955 profile to the database. The RT955 isolates were characterised by whole genome sequencing and tested for susceptibility to 15 antimicrobials. Results We did not find RT955 in Czech (n = 6,661, 2012–2023) and Slovak (n = 776, 2015–2023) isolates, but identified 13 RT955 cases (n = 303, 2021–2023) in three hospitals in Poland. By whole genome multilocus sequence typing, 10 isolates clustered into one clonal complex including a sequence of United Kingdom strain ERR12670107, and shared similar antimicrobial resistance genes/mutations. All 13 isolates were resistant to ciprofloxacin/moxifloxacin, erythromycin/clindamycin and ceftazidime. All isolates had a mutation in the nimB gene promoter and in NimB (Tyr130Ser and Leu155Ile). The metronidazole resistance was detected in all isolates using brain-heart-infusion agar supplemented with haemin and Chocolate agar. Results were discrepant with the European Committee on Antimicrobial Susceptibility Testing-recommended Fastidious anaerobe agar and Brucella blood agar. Conclusion The identification of clonally related haem-dependent metronidazole-resistant C. difficile RT955 in multiple hospitals indicates a need for prospective surveillance to estimate its prevalence in Europe.